2017
DOI: 10.1080/15459624.2017.1388512
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of area and personal breathing zone concentrations of diesel particulate matter (DPM) during oil and gas extraction operations, including hydraulic fracturing

Abstract: Diesel engines serve many purposes in modern oil and gas extraction activities. Diesel particulate matter (DPM) emitted from diesel engines is a complex aerosol that may cause adverse health effects depending on exposure dose and duration. This study reports on personal breathing zone (PBZ) and area measurements for DPM (expressed as elemental carbon) during oil and gas extraction operations including drilling, completions (which includes hydraulic fracturing) and servicing work. Researchers at the National In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Mining and oil and gas extraction (OGE) are industries with chronically poorer health compared with the general working population 1–8 . Data from the National Institute for Occupational Safety and Health (NIOSH)National Occupational Mortality Surveillance (NOMS) system have demonstrated excessive mortality in miners from heart disease, renal disease, and several types of cancers, including laryngeal, prostate, bladder, and kidney 9 ; and in OGE workers, from Parkinson's disease, heart disease, and cancers (mesothelioma, prostate, bladder, and kidney) 10…”
Section: Introductionmentioning
confidence: 99%
“…Mining and oil and gas extraction (OGE) are industries with chronically poorer health compared with the general working population 1–8 . Data from the National Institute for Occupational Safety and Health (NIOSH)National Occupational Mortality Surveillance (NOMS) system have demonstrated excessive mortality in miners from heart disease, renal disease, and several types of cancers, including laryngeal, prostate, bladder, and kidney 9 ; and in OGE workers, from Parkinson's disease, heart disease, and cancers (mesothelioma, prostate, bladder, and kidney) 10…”
Section: Introductionmentioning
confidence: 99%
“…DPM was used in this study to mimic the background carbonaceous interfering agent, because it is present in many workplace aerosols , and may potentially interfere with selective CNT measurement. Raman spectra of the certified DPM standard and the corresponding calibration curves are shown in Figure S5.…”
Section: Resultsmentioning
confidence: 99%
“…Since this historical air pollution episode, a large number of studies have demonstrated the association between air pollution and human disease including respiratory and lung diseases such as chronic obstructive pulmonary disease, asthma attacks, pulmonary cancer, leukemia, birth defects and immune system defects, cardiovascular problems, heart disease and stroke, neurobehavioral disorders, and liver and other types of cancer [ 4 18 ]. Diesel combustion to generate power has existed for well over a century and is used in heavy machinery such as large trucks and oil tankers [ 19 22 ]. The mechanism by which diesel exhaust impacts human health is being studied extensively [ 23 31 ].…”
Section: Introductionmentioning
confidence: 99%